Penerapan Media Permainan Ular Tangga Untuk Meningkatkan Hasil Belajar IPS Siswa Kelas V : (Studi Pada SDK Kekawii Kabupaten Ende) - Kristina Djo (Program Studi Pendidikan Ekonomi, Universitas Flores, 2021)
This study aims to determine the increase in student interest in learning by applying the snake and ladder game media. This type of research includes Classroom Action Research (PTK). Data collection techniques using observation techniques, questionnaires, tests, documentation, and field notes. The collected data were analyzed descriptively qualitatively and descriptively quantitatively. The results showed that the snake and ladder game media can increase interest in learning and learning outcomes. This can be seen from the observation percentage of students 'interest in learning who reach the fairly active and very active categories, namely 51 percent in cycle I to 90 percent in cycle II and the percentage of students' interest in learning who reach the category of sufficiently interested and very interested, namely 60 percent in cycle I to 85 percent in cycle II. Learning outcomes also increased from the percentage of classical completeness, namely 54 percent in cycle I to 100 percent in cycle II.